2005
DOI: 10.1007/s10677-005-8242-9
|View full text |Cite
|
Sign up to set email alerts
|

Living Well with End Stage Renal Disease: Patients' Narratives Interpreted from a Virtue Perspective

Abstract: Over the last few decades there has been a revival of interest in virtue ethics, with the emphasis on the virtuous caregiver. This paper deals with the 'virtuous patient', specifically the patient with End Stage Renal Disease (ESRD). We believe that a virtue approach provides insights not available to current methods of studying coping styles and coping strategies. Data are derived from seven semi-structured in-depth interviews. The transcripts of the interviews were subjected to an Interpretative Phenomenolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
2
9
0
5
Order By: Relevance
“…This finding is consistent with the findings of studies of patients with ESRD on HD in the United States, Greece, Hong Kong, Australia, and the Netherlands (Al-Arabi, 2006;Dekker et al, 2005;Kaba et al, 2007;Suet-Ching, 2001). The researchers in these previous studies reported that the most troublesome restrictions that patients with ESRD experienced were physical limitations that adversely affected their QOL, followed by dependence on others, loss of familiar role functions, changes in lifestyle, lowered self-esteem, feelings of helplessness, and alterations in family dynamics.…”
Section: Facing Life's Limitationssupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is consistent with the findings of studies of patients with ESRD on HD in the United States, Greece, Hong Kong, Australia, and the Netherlands (Al-Arabi, 2006;Dekker et al, 2005;Kaba et al, 2007;Suet-Ching, 2001). The researchers in these previous studies reported that the most troublesome restrictions that patients with ESRD experienced were physical limitations that adversely affected their QOL, followed by dependence on others, loss of familiar role functions, changes in lifestyle, lowered self-esteem, feelings of helplessness, and alterations in family dynamics.…”
Section: Facing Life's Limitationssupporting
confidence: 92%
“…Many qualitative studies have described the experiences of living with ESRD (Al-Arabi, 2006;Dekker et al, 2005;Kaba et al, 2007;Suet-Ching, 2001). It has been reported that patients with ESRD worry about the integrity of their vascular access (Gokal & Hutchison, 2002;Lindqvist, Carlsson, & Sjö dén, 1998;Polaschek, 2003).…”
Section: Living With Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“… 61 152 To demonstrate resilience, some patients tried to maintain a sense of normalcy, integrating the dialysis community into their social network. 42 139 210 260 …”
Section: Resultsmentioning
confidence: 99%
“…Hagren et al (2001Hagren et al ( , 2005 interviewed Swedish ESRD patients and identified the existing struggle imposed by prolonged haemodialysis treatment, including the negative impact of life restrictions and use of time. Dekker et al (2005) described the moral challenges of living with ESRD for Dutch patients, and Lin et al (2005) explored the process of decision-making regarding haemodialysis for 12 Taiwanese individuals. Only the latter study actively considered the impact of culture and the haemodialysis experience.…”
Section: Background and Aimsmentioning
confidence: 99%